Strategi Peningkatkan Profesionalisme Guru di Era Globalisasi - Chusnul Khotimah (Fakultas Tarbiyah dan Ilmu Keguruan (FTIK) Institut Agama Islam Negeri (IAIN) Metro, 2019)
This article describes a strategy for increasing teacher professionalism in the era of globalization. In this era, teachers have more complex tasks and functions, so they need to have standard competence and professionalism. A professional teacher does not only carry out learning in the classroom, but educates, nurtures, guides, and shapes the personality of his students so that they have critical and creative human resource development. Teachers who come from the pre-digital world find it difficult to build effective communication with students from the digital age. Habits and ways of learning are different from old habits. This phenomenon often makes teachers and students confused, even frustrated. Therefore, there needs to be something to connect it, which is a strategy to improve teacher professionalism in facing challenges in the digital age. Strategies The continuous development of the teaching profession is intended to stimulate, maintain and improve teacher competence in solving educational and learning problems that have an impact on improving quality. Therefore, increasing teacher competency can carry out tasks and responsibilities in a professional manner, becoming a very urgent need.